Comparing infection control and ward nurses' views of the omission of infection control activities using the Missed Nursing Care Infection Prevention and Control (MNCIPC) Survey. (11th February 2021) - Henderson, Julie; Willis, Eileen; Blackman, Ian; Verrall, Claire; McNeill, Liz
Abstract: Aim: To compare the perceptions of nurses with infection control expertise and ward nurses as to what infection control activities are missed and the reasons why these activities are omitted. Background: Infection prevention activities are viewed as important for reducing health care‐acquired infections (HAIs) but are often poorly performed. Methods: Data were collected through the Missed Nursing Care Infection Prevention and Control (MNCIPC) Survey delivered to 500 Australian nurses prior to COVID‐19. Results: Significant differences were found on the mean scores between infection control and other nurses on ten items. In eight cases, five relating to hand hygiene, infection control specialists viewed the activity as more likely to be missed. Factors viewed as having greater contribution to omission of infection control prevention were as follows: 'Patients have to share bathrooms', 'Urgent patient situation' and 'Unexpected rise in patient volume and/or acuity on the ward/unit'. Infection control nurses were more likely to highlight the role of organisational and management factors in preventing effective infection control. Conclusions: Differences in response between nurses suggest that the extent of omission of infection control precautions may be under‐estimated by ward nurses. Implications for Nursing Management: Infection control specialists are more likely to identify organisational barriers to effective infection control than other nurses. Work demands arising from pandemic management may contribute to infection control precautions being missed.